Composition , Voices , and the Poetological Programme in the Carmina Anacreontea - Bär, Silvio (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2016)
In this article it is argued that various (and partly conflicting) voices of different speakers emerge from the Carmina Anacreontea and that they invite the readers to actively engage in a productive dialogue with the collection.